The impact of international trade on the price of solar photovoltaic modules: empirical evidence - Ivan Hajdukovic (EconomiA, 2023)
Purpose: Over the past decades, the global solar photovoltaic (PV) market has experienced an unprecedented development associated with a substantial decline in solar PV module prices. A body of literature has attempted to identify and evaluate the different sources of price variation. However, the impact of international trade on the price of solar PV modules has not yet been empirically examined. This paper contributes to filling this gap in the literature by providing a comprehensive empirical examination on the relationship between international trade and solar PV module prices. Design/methodology/approach: The author uses a sample of 15 countries over the period 2006-2015 and proposes a linear dynamic panel data model based on a new specification, including a number of relevant factors influencing solar PV module prices. Findings: The empirical analysis reveals that an increase in imports of solar PV cells and modules is associated with a decline in solar PV module prices. This finding suggests that international trade could lead to further price reductions, thus fostering the deployment of solar PV technology. The study reveals several other important findings. Market and technological development are key factors explaining the decline in solar PV module prices. Moreover, government policies such as public budget for R&D in PV and feed-in tariff for solar PV are effective in reducing the price of solar PV modules. Originality/value: This paper examines the influence of international trade, government policies, market development and technological development on solar PV module prices. The results may be of interest to both academic research and policy analysis.
Keywords: C23; F18; Q42; Q56; 330; Dynamic panel data models; Solar photovoltaic module prices; Trade and environment